2014
DOI: 10.1063/1.4883755
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon superconductivity in LaO0.5F0.5BiSe2

Abstract: Articles you may be interested inGrain size modification in the magnetocaloric and non-magnetocaloric transitions in La0.5Ca0.5MnO3 probed by direct and indirect methodsWe report density functional calculations of the electronic structure, Fermi surface, phonon spectrum and electron-phonon coupling for the newly discovered superconductor LaO 0.5 F 0.5 BiSe 2 . It is confirmed that there is a strong Fermi surface nesting at (p,p,0), which results in unstable phonon branches. Combining the frozen phonon total en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
2
25
1
Order By: Relevance
“…Despite the similar structural configuration, BiS(Se) 2 -based layered superconductors exhibit some important differences comparing with Fe-pnictide superconductors, and the superconducting mechanism remains unclear. Theoretical calculation suggests that LaO 0.5 F 0.5 BiSe 2 and LaO 0.5 F 0.5 BiS 2 belong to conventional electronphonon coupling induced superconductors [13][14][15][16]; g-wave [17] and s-wave [18][19][20] pairing symmetries have been proposed by different groups. Physical measurement shows that the parent compound LnOBiS 2 is a bad metal without detectable antiferromagnetic transition or structure phase transition, implying that magnetism is of less importance to superconductivity in BiS 2 -based systems [7], and the superconductivity appears in close proximity to an insulating normal state for the optimal superconducting samples, in sharp contrast to the iron-based superconductors where superconductivity grows from a metallic state [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similar structural configuration, BiS(Se) 2 -based layered superconductors exhibit some important differences comparing with Fe-pnictide superconductors, and the superconducting mechanism remains unclear. Theoretical calculation suggests that LaO 0.5 F 0.5 BiSe 2 and LaO 0.5 F 0.5 BiS 2 belong to conventional electronphonon coupling induced superconductors [13][14][15][16]; g-wave [17] and s-wave [18][19][20] pairing symmetries have been proposed by different groups. Physical measurement shows that the parent compound LnOBiS 2 is a bad metal without detectable antiferromagnetic transition or structure phase transition, implying that magnetism is of less importance to superconductivity in BiS 2 -based systems [7], and the superconductivity appears in close proximity to an insulating normal state for the optimal superconducting samples, in sharp contrast to the iron-based superconductors where superconductivity grows from a metallic state [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a new superconductor LaO 0.5 F 0.5 BiSe 2 with the same structure as the LaO 0.5 F 0.5 BiS 2 was discovered with T c ∼ 3.5 K [29][30][31]. It was reported that the electronic structure and Fermi surface in these two compounds are quite similar [32]. Since the system now is selenium based, it is highly desired to do investigations on BiSe 2 -based materials, better in form of single crystals.…”
mentioning
confidence: 99%
“…In some theoretical calculations, possible CDW that is caused by Peierls mechanism has been proposed. From these theoretical calculations in LaO 1-x F x BiSe 2 , following features are expected.(i) The instability against CDW formation is expected to develop alongdirection in the k space [44].(ii) This instability of CDW is enhanced at the F concentration of 0.5, where Fermi surfaces connect [34][35][36][37].(iii) A period of the predicted CDW is expected to be √2 times of the lattice constant a 0, which is corresponding to the nesting vector along direction.The observed supermodulation is consistent with features (i) and (ii). On the other hand, the observed period of about 5 times of the lattice constant a 0 is inconsistent with (iii).…”
mentioning
confidence: 88%